Tales from India : stories of creation and the cosmos - Gavin, Jamila; Hall, Amanda (Somerville, Mass. : Templar Books, 2011)
An illustrated collection of Hindu tales that features stories of the birth of the gods, the creation, the arrival of humans, great floods, romances, and battles between good and evil.
Kirkus Review, August 2011
6.5
5-8
Keywords: Hindu mythology -- Juvenile literature; Hindu mythology